Analisis Pengaruh Efisiensi BOPO dan Manajemen NPL terhadap Nilai Pasar Saham pada 10 Perbankan yang Terdaftar di Bursa Efek Indonesia (BEI): Analysis of the Effect of BOPO Efficiency and NPL Management on Stock Market Value in 10 Banks Listed on the Indonesia Stock Exchange (IDX) - Oyon Wiharto; Ramadhan Imam Hartoyo; Dini Avlia; Miftahul Jannah (PT Cakrawarti Empat Proksi, 2026)
In the economic sector, banks serve as financial intermediaries whose stability is heavily influenced by global economic fluctuations. The importance of maintaining fundamental performance often reveals a research gap between theories of bank soundness and the actual response of stock prices in the capital market. This study aims to re-examine the impact of operational efficiency—measured by the Operating Expenses to Operating Income (BOPO) ratio—and Non-Performing Loan (NPL) management on the stock prices of 10 banking companies listed on the Indonesia Stock Exchange (IDX) during the quarterly periods of 2025. A quantitative method utilizing secondary data was employed, with purposive sampling yielding 40 observations. Following a Cochrane-Orcutt transformation to address autocorrelation, the effective number of observations became 39. Data analysis was conducted using multiple linear regression with the aid of SPSS 23. Partial test results indicate that BOPO efficiency has a significant negative effect on stock prices, whereas NPL management does not have a significant partial effect on banking stock prices. However, the F-test reveals that BOPO and NPL collectively have a significant effect on stock market value at a significance level of 0.005. An R-squared value of 0.213 indicates that these two independent variables contribute 21.3% to the explanation of stock price variations, with the remainder attributed to other factors. These findings suggest that operational efficiency, as reflected in the BOPO ratio, is a primary factor for investors in determining the market value of banking stocks, outweighing the impact of non-performing loan (NPL) levels